Deceptive Character in Peter Shaffer’s Play “Black Comedy” a Psychoanalysis Approach - Amy Angelina; Suparto Suparto (ITScience (Information Technology and Science), 2023)
This research discusses about the deceptive characters from Peter Shaffer's plays Black Comedy with a psychoanalysis approach. The aims of this research are to identify the personality traits of deceiver and describe the characteristic of deception in the deceptive characters using Alder Vrij's theory of deception. The method that is used in this research is qualitative research method which all data are analyzed in the form of words and sentences. The source data is from drama script of Black Comedy by Peter Shaffer. The results of this research are Brindsley’s personality traits as a deceiver. The characteristics of deception that are found through Brindsley’s character namely, processes of lying and the behavior of liar.